The Response To Multifunctional Fertilizer And Cow Manure Growth And Production Of Sedele Plant (Glysine Max L) - Sulardi, Sulardi; M. Wasito; Agnes Refiana Sembiring (SEAN Institute, 2024)
The purpose of this study was to determine the response of multifunctional fertilizer and cow dung on the growth and production of Soybean (Glycine max L.) plants and their interactions. This study was conducted in Klambir Lima Hamparan Perak Village, Deli Serdang Regency, North Sumatra from January to March 2023, using a factorial Randomized Block Design (RAK), with three blocks, 12 combinations. The first factor is cow dung fertilizer (P0) = 0 kg/plot, (P1) = 1.5 kg/plot, (P2) = 3 kg/plot, and (P3) = 4.5 kg/plot. The second factor is ecoenzyme (E1) = 90 ml/plot, (E2) = 180 ml/plot and (E3) = 270 ml/plot. The parameters observed were plant height (cm), number of productive branches (branches), number of pods per sample (plong), number of plong per plot (pods), production per sample (g) and production per plot (g). The results of the study showed that the provision of cow dung fertilizer had an effect on all observation parameters. The best observation parameter results on soybean plants were in the P3 = 4.5 kg / plot treatment. The provision of multifungal fertilizer on the growth and production of soybean plants had an effect on all observation parameters. With a treatment of 270 ml / plot gave the best results on soybean plants, while the interaction between cow dung fertilizer and ecoenzyme had no significant effect on all observation parameters.